Auditors' Incentives and Their Application of Financial Accounting Standards - Hackenbrack, Karl; Nelson, Mark W. (The Accounting Review, 1996)
[We report on an experiment in which experienced auditors (1) determine whether to allow a client to adopt an aggressive reporting method when the auditors have an incentive to do so, and (2), justify aggressive reporting by their interpretations of financial accounting standards. In the experiment, the appropriate reporting method depends upon whether an amount can be "reasonably estimated" as that term is used in an applicable accounting standard. The accounting standard relevant to determining the appropriate reporting method was manipulated between subjects (thus varying whether judging that an amount can be reasonably estimated would justify an aggressive or conservative method), as was engagement risk. The results indicate that the auditors responded to moderate engagement risk by permitting the aggressive reporting method and justified their choice with aggressive interpretations of accounting standards. When faced with high engagement risk, the auditors responded by requiring conservative reporting and justified their choice with conservative interpretations of accounting standards.]